RAXBAR KADRLARNING INNOVATSION YETAKCHILIGINING IJTIMOIY PSIXOLOGIK XUSUSIYATLARI - Saparov, Sh.B.; Nurabullaev, T.A. (SCIENCE and SOCIETY, 2024)
In this article, it is analyzed the main socio-psychological characteristics necessary for successful innovative leadership of senior personnel, and considered practical recommendations for their development and improvement.
Keywords: socio-psychological skills; innovative leadership; active listening; conflict management; self-development; successful specialist; skill development; practice